1982
DOI: 10.1161/01.cir.65.2.248
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow reductions in stenosed canine coronary arteries: vasospasm or platelet aggregation?

Abstract: SUMMARY In 67 dogs with a 60-80% coronary stenosis produced by an external constricting plastic ring, blood flow measured with an electromagnetic flowmeter showed cyclical flow reductions of varying magnitude and duration, and then an abrupt return to control flow. In 45 dogs, heparin did not prevent these flow reductions, but ibuprofen (Motrin) or indomethacin abolished them. With incremental doses of each of these drugs, the cyclical flow reductions and the platelet function in vitro were diminished proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(83 citation statements)
references
References 15 publications
(4 reference statements)
8
75
0
Order By: Relevance
“…17,18 The nadir of flow during periods of cyclic flow reduction, often to zero flow, coincides with the presence of obstructive platelet-rich thrombi, 15,16 as is also apparent in our study, in which obstructive thrombi were seen in all cases of zero flow. The platelet dependency of CFVs is stressed by their exquisite sensitivity to antiplatelet agents.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…17,18 The nadir of flow during periods of cyclic flow reduction, often to zero flow, coincides with the presence of obstructive platelet-rich thrombi, 15,16 as is also apparent in our study, in which obstructive thrombi were seen in all cases of zero flow. The platelet dependency of CFVs is stressed by their exquisite sensitivity to antiplatelet agents.…”
Section: Discussionsupporting
confidence: 86%
“…CFVs in stenosed arteries reflect the dynamic process of growth and embolization of platelet-rich thrombi, with the rate of flow reduction being proportional to the rate of platelet accumulation in the narrowed lumen, 15,16 and have been observed in patients during the course of acute coronary syndromes. 17,18 The nadir of flow during periods of cyclic flow reduction, often to zero flow, coincides with the presence of obstructive platelet-rich thrombi, 15,16 as is also apparent in our study, in which obstructive thrombi were seen in all cases of zero flow.…”
Section: Discussionmentioning
confidence: 99%
“…48 Evidence indicates that reductions in blood flow are due to the interactions of platelets with the vessel wall and with each other, leading to vascular occlusion. 49 The technique, developed originally in dogs, has been used in other species, including monkeys. 34,50 Although this model does not require the presence of atherosclerotic plaque and does not directly mimic what happens during plaque rupture, it, like other injury thrombosis models, causes intimal injury and exposes subintimal components to circulating blood in a setting of altered blood flow.…”
Section: Cynomolgus Monkey Modelmentioning
confidence: 99%
“…34 - 35 In contrast, in arteries with denuded endothelium, platelets produce contraction that appears to be mediated by thromboxane and serotonin. 35 Several studies indicate that aggregation of platelets can reduce blood flow, 8 11 demonstrated a cyclic reduction in coronary blood flow in dogs caused by periodic formation of platelet aggregates at the site of endothehal injury followed by spontaneous dissolution. This cyclic flow reduction is mediated by a cyclooxygenase-dependent pathway, and active vasoconstriction did not seem to contribute to the reduction in flow because nitrogh/cerin failed to affect the cyclic reductions in blood flow.…”
Section: Mechanisms Of Altered Vascular Response To Activated Plateletsmentioning
confidence: 99%
“…8 Reductions in flow result from intracoronary deposition of platelets that may trigger vasoconstriction, largely mediated by TxA 2 , serotonin, 9 and ADP 10 that are released by activated platelets. It is not clear, however, whether reductions in flow are mediated by mechanical obstruction by aggregated platelets, 11 or whether platelet-induced vasoconstriction may contribute to reductions in blood flow.…”
mentioning
confidence: 99%